An easily and environmentally friendly accessible small-molecule acetylenic donor for organic solar cells. (January 2019) - Zhang, Chun-Hui; Yu, Pan-Pan; Tan, Wan-Yi; Luo, Dou; Wang, Li-Ping; Xia, Yan; Liu, Chun-Chen; Cao, Yong
Abstract: Photovoltaic aryl acetylenes may provide a green access to high performance electron donors for organic solar cells. Here we describe a solution-processable acetylenic molecule An(DTDPPA)2, which consists of a central anthracen-9, 10-diyl unit and two dithienyldiketopyrrolopyrrole endgroups via acetylenic linkages. It's worth noting that the acetylenic linkages in An(DTDPPA)2 enable facile and green accessibility through Sonogashira reactions with atypically high yield and atom efficiency. In solid film An(DTDPPA)2 features an absorption peak at 630 nm with an emerging shoulder at 686 nm. The HOMO/LUMO level of An(DTDPPA)2 is estimated as −5.18/-3.62 eV according to cyclic voltammetry and the optical absorption onset. Due to the highly coplanar configuration and close packing, the hole mobility of the thermally annealed film of An(DTDPPA)2 was improved to as high as 9.30 × 10 −4  cm 2  V −1  s −1 . In combination with PC61 BM, the bulk heterojunction solar cells provide a power conversion efficiency of 5.26% utilizing no processing additive or solvent vapor annealing. The results are carefully discussed in comparison to the related compounds without the acetylenic linkage and based on the DFT molecular modeling. The demonstrated dramatic effects of acetylenic linkages in this work may encourage and motivate more efforts to design easily accessible and eco-friendly organic semiconductors. Graphical abstract: Introducing the acetylenic linkages endows the target compound with a coplanar configuration, narrowed bandgap, broadened absorption, higher hole mobility. This result indicates an effective chemical tailoring strategy to achieve cost-effective and facilely accessible high performance small-molecule donors and efficient organic photovoltaic cells without using high-boiling-point solvent additive or solvent vapor annealing. Image 1 Highlights: An acetylenic small-molecule donor is prepared by facile and green synthesis. Modified work-up procedure for preparing 9, 10-diethynylanthracene is presented. Modification effects of acetylenic linkages are systematically investigated. An impressive PCE of 5.26% is obtained, involving no solvent additives or SVA.